Investigation of Physical Properties of Basalt Stones in the Southeast Anatolian Region of Turkey - Yıldız, Servet; Işık, Nursen; Keleştemur, Oğuzhan (My University, 2008)
In this study the physical properties of basalt stones, which were picked up from three different regions according to their spread fields in the Diyarbakır-Karacadağ, which is located in the Southeast Anatolian Region of Turkey, have been investigated. Density, water absorption and drying tests, durability of natural freezing effects, and compressive strength after freezing and freeze loss test with sodium sulfate have been carried out in order to determine the physical properties of the basalt stone specimens. As a result of this study, it has been determined that Diyarbakır Karacadağ Basalts are an important material for architecture constructions and can resist to external effects since the test results is not exceeding the limit given in TS 699.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Basalt stone; Physical properties; Freeze loss